Root Depth Isn’t What It Used To Be - Evan G. Johnson; Lorenzo Rossi; Tanyaradzwa Chinyukwi; Davie Kadyampakeni (EDIS, 2021)
The detrimental effect of Huanglongbing (HLB) on roots has changed how we think about root health and horticultural management of citrus in Florida. As part of the work studying nutritional responses described earlier in this issue, we have been studying the effects of macronutrient and micronutrient fertilization on root health. The most common way to estimate root health is based on root density with soil cores. This gives a snapshot of the root uptake capacity in the sampled soil, normally the top 10 inches in citrus irrigated with microjets. In this factorial study of different amounts of macronutrients and micronutrients, we used minirhizotrons (clear plastic tubes) with a root scanner to measure root growth and dieback monthly since shortly after the fertilizer treatments began.